Strategy Design in a Digital Ecosystem The Ecosystem Growth and Collaboration (EGC) Model - Jan-Frederik Engelhardt; Sebastian Badde (Marketing Review St.Gallen, 2021)
There is rising concern among executives to align their strategy to the increasingly digital and connected business environment – what is termed the 'digital ecosystem'. This article offers a framework – the Ecosystem Growth and Collaboration (EGC) model – to understand and integrate digital ecosystem mechanisms into a corporate strategy. These growth and collaboration mechanisms form the basis to decide where, in which role, and how to play in the digital cosmos.
Keywords: 650